The Institutes of Gaius and Rules of Ulpian : the former from Studemund's apograph of the Verona Codex : with translation and notes, critical and explanatory, and copious alphabetical digest - Gaius; Gaius; Ulpianus, Domitius, approximately 160-228; Ulpianus, Domitius, approximately 160-228; Studemund, Wilhelm, 1843-1889; Muirhead, James, 1831-1889 (LLMC-digital (Series), 1880)
The Institutes of Gaius and Rules of Ulpian : the former from Studemund's apograph of the Verona Codex, with translation and notes, critical and explanatory, and copious alphabetical digest : by James Muirhead, Professor of Civil Law at the University of Edinburgh, originally intended to simply incorporate the notes from his copy of the Institutional Commentaries of Gaius for use by his students. The work includes the Latin text with the English translation on the alternative sections of the pages. The Introduction includes what he feels is necessary for students to know of Gaius and his Institutes and Studemund's Apograph. A Table of Authorities cited in the Notes by their abbreviation begins on page xvii and a subject index begins on page 441.